2021
DOI: 10.3390/cells10050986
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells and Skin and Breast Cancers: A Complicated and Microenvironment-Dependent Role

Abstract: Mast cells are important sentinel cells in host defense against infection and major effector cells in allergic disease. The role of these cells in cancer settings has been widely debated. The diverse range of mast cell functions in both immunity and tissue remodeling events, such as angiogenesis, provides multiple opportunities for mast cells to modify the tumor microenvironment. In this review, we consider both skin and breast cancer settings to address the controversy surrounding the importance of mast cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 191 publications
0
15
0
3
Order By: Relevance
“…By tissue remodeling, Mast cells promoting vessel formation through constitutive and immunologically mediated release of angiogenic substances such as VEGF-A, CXCL16, Endothelin-1, GM-CSF, CXCL8, and CCL2. So Mast cells play an important role in tumor development and immune therapy [15]. Thus, the positive in uence of NXNL1 on BC are consistence with the role of higher abundance of NK cells and Mast cells, which indicates a possible mechanism where NXNL1 effects the overall survival of BC.…”
Section: Discussionmentioning
confidence: 99%
“…By tissue remodeling, Mast cells promoting vessel formation through constitutive and immunologically mediated release of angiogenic substances such as VEGF-A, CXCL16, Endothelin-1, GM-CSF, CXCL8, and CCL2. So Mast cells play an important role in tumor development and immune therapy [15]. Thus, the positive in uence of NXNL1 on BC are consistence with the role of higher abundance of NK cells and Mast cells, which indicates a possible mechanism where NXNL1 effects the overall survival of BC.…”
Section: Discussionmentioning
confidence: 99%
“…CAF induce the differentiation of tumor-associated mast cells (MC), which are known to induce angiogenesis and modulate chronic inflammation [ 136 ] and potentially cancer cell growth [ 165 ].…”
Section: Immune Cell Dynamics and Car-t Anticancer Responsementioning
confidence: 99%
“…Neoplastic B cells may also modify the activities of mast cells such as recruitment and activation. This is in addition to a multitude of less B cell specific interactions between mast cells and tumours that occur in tumour settings (94)(95)(96)(97). For example, Fischer et al (98) have shown that neoplastic cells from Hodgkin's Lymphoma secrete CCL5 at sites of infiltration to recruit mast cells.…”
Section: Mast Cell/b Cell Interaction and Co-localisationmentioning
confidence: 99%